Efficacy of a bioactive material and nanostructured desensitizing on dentin hypersensitivity treatment - Bevilacqua, Flávia Magnani; Catelan, Anderson; AraÚjo, Giovana Spagnolo Albamonte; Saraceni, Cintia Helena Coury; Sampaio, José Eduardo Cézar (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction Dentin hypersensitivity is a frequent occurrence in dental practice. It is clinically characterized by acute, short, and temporary pain in response to mechanical, chemical, thermal, or osmotic stimuli resulting from dentin exposure.Objective To compare in vivo the effect of an experimental crystalline bioactive material and nanostructured desensitizing on the pain assessment among patients with cervical dentin hypersensitivity.Material and method Thirty patients were selected for this study, who were randomly assigned to two groups (n=15) in a split-mouth design. Each patient received two treatments: group 1 (fluoride gel and bioactive material) and group 2 (fluoride gel and nanostructured desensitizing). Pain analyses were performed using a visual analogue scale, ranging 0-10. Baseline pain measurement was performed prior to initial treatment (T0) and new measurements were carried out weekly for 3 weeks (T1, T2, and T3) before materials were reapplied. Final pain analysis was performed 3 months after initial treatment (T4). Degree of pain reduction was calculated using the formula T0 - Tperiod after treatment. The data of the pain measurements were analyzed using 2-way repeated measure ANOVA and Tukey’s test (α=0.05).Result Regardless of evaluation period, there was no statistical difference on pain reduction between the treatments (p>0.05). The degree of pain was reduced significantly in each evaluated period for all tested treatments (p<0.05), by approximately three degrees after 3 months.Conclusion The tested desensitizing materials were effective on dentin hypersensitivity reduction.

ResumoIntrodução A hipersensibilidade dentinária é uma ocorrência frequente na prática clínica; clinicamente caracterizada por dor aguda, curta e temporária, em resposta ao estímulo mecânico, químico, térmico ou osmótico causada pela exposição dentinária.Objetivo Comparar in vivo o efeito de um material bioativo cristalino experimental e um dessensibilizante nanoestruturado na avaliação da dor de pacientes com hipersensibilidade dentinária cervical.Material e método Trinta pacientes foram selecionados para este estudo, que foram randomicamente divididos em dois grupos (n=15) em um desenho experimental de boca dividida. Cada paciente recebeu dois tratamentos: grupo 1 (flúor gel e material bioativo) e grupo 2 (flúor gel e dessensibilizante nanoestruturado). As análises de dor foram realizadas usando uma escala visual analógica, variando de 0-10. A mensuração da dor inicial foi realizada previamente ao tratamento inicial (T0) e novas análises foram realizadas semanalmente durante 3 semanas (T1, T2 e T3) antes da reaplicação dos materiais. A análise final da dor foi realizada 3 meses após o início do tratamento (T4). O grau de redução de dor foi mensurado pela fórmula: T0 - Tperíodo após tratamento. Os dados das mensurações de dor foram analisados pela ANOVA para medidas repetidas 2 critérios e teste de Tukey (α=0,05).Resultado Independente do período de avaliação, não houve diferença estatística entre todos os tratamentos na redução da dor (p>0,05). O grau de dor reduziu significativamente em cada período avaliado para todos os tratamentos testados (p<0,05), aproximadamente três graus após 3 meses.Conclusão Os materiais dessensibilizantes testados foram efetivos na redução da hipersensibilidade dentinária.
Eficácia de um material bioativo e dessensibilizante nanoestruturado no tratamento da hipersensibilidade dentinária
Keywords: Dentin desensitizing agents; dentin sensitivity; pain; Dessensibilizantes dentinários; sensibilidade da dentina; dor